Advanced practice role delineation within Finland: A comparative descriptive study. (15th October 2021) - Jokiniemi, Krista; Heikkilä, Asta; Meriläinen, Merja; Junttila, Kristiina; Peltokoski, Jaana; Tervo‐Heikkinen, Tarja; Mattila, Elina; Mikkonen, Santtu
Abstract: Aim: To identify and differentiate the practice patterns of generalist, specialist and advanced practice nursing roles in specialist and central hospital contexts. Background: In Finland, as in other Nordic countries, advanced practice nursing roles emerged around 2000. There are over 60, 000 registered nurses/midwives in Finland and the clinical career pathway from a registered nurse to advanced practice nurse has been described yet not fully implemented in healthcare organizations. However, the number and activities of nonadvanced and advanced practitioner roles are not well known. Design: A descriptive comparative study. Methods: An online self‐report survey was conducted between August and October 2020 using an advanced practice role delineation tool. A census sample of registered nurses, registered midwives, specialist nurses and advanced practice nurses in five university hospitals and one central hospital was recruited. Descriptive statistics were used to summarize the characteristics of participants and group differences were compared using analysis of variance (ANOVA). The STROBE checklist was used as the reporting guideline. Results: A total of 1497 responses were obtained (response rate = 10%). Overall, nurses used comprehensive care and education activities most frequently. The least used activities were research and publication and professional leadership. Univariate analysis of variance test between role effects, when education and grouped age were taken into account, showed statistically significant difference in all of the observed five activities ( p < .001). Conclusion: Identifying activities in different levels of nursing is a crucial first step in delineating nursing roles thus improving the governance of the human resource management. Impact: The study results add to the international literature, delineating nursing roles in the spectrum of generalist to advanced practice nursing. As these roles become more formalized, we may incorporate novel ways of promoting the career development and optimal use and assessment of nursing roles and practice in various career levels.